Respuesta :

Answer:

 (146 +  0i)

Step-by-step explanation:

(11+5i)(11-5i)

The formula is :

(a+bi) • (x+yi)  = ax+by•i^2+(ay+bx)i

and since  i^2 = -1  it can be written as :

ax - by + (ay + bx) i

( 11 +  5i) • ( 11 -  5i) =

 (146 +  0i)

hope this helped brainlest owo???

Answer:

146

Step-by-step explanation:

(11 + 5i)(11 - 5i) =

Use the product of a sum and a difference, (a + b)(a - b) = a^2 - b^2.

= 11^2 - (5i)^2

= 121 - (25)(i^2)

= 121 - (25)(-1)

= 121 - (-25)

= 121 + 25

= 146